MEKTEPKE ShEKEMGI BILIMLENDIRIW ShÓLKEMLERINDE BILIM BERIW OYÍNLARI HÁM OLARDIŃ ÁHMIYETI - Tóremuratova, D.M. (SCIENCE and SOCIETY, 2025)
The article discusses games, which are the main type of children's activity, and types of games. Educational games and their features, their role in child development are discussed.